Green Marketing and the Decision to Purchase Sustainable Cosmetic Products: A Case Study Applied to Millennial Consumers - María del Pilar MIRANDA-GUERRA; Naomi Francesca AVILA ARELLANO; Jenny Merly GARAY CONDORACHAY; César Enrique VERASTEGUI RAMOS (Communications of International Proceedings, 2023)
Traditional marketing practices have lost impact because they do not consider as differentiating elements the factors generated by the evolution of society, such as the growing evolution of environmental awareness on the part of consumers, aligned with the depredation of our planet. In response to this problem, the concept of green marketing (GM) arises, which links marketing strategies with practices that ensure the preservation of the ecosystem and appeals to the environmental awareness of consumers and its impact on the purchase decision process (PDP). The main objective of this study is to determine the relationship between GM and its dimensions in the variable Decision to Purchase Cosmetic Products in Millennial consumers, Northern Lima - 2022. The methodology has a cross-sectional, non-experimental approach and descriptive scope. The sample consisted of 384 millennials, to whom a validated questionnaire that addresses the variables described was applied. The results found a positive relationship between GM and PDP, which is confirmed by Spearman's Rho correlation statistical test (Rho=0.371, Sig. (Bilateral) =0.000; (p ≤0.000). Regarding the dimensions of GM and its relationship with PDP, it was found: product (Rho = 0.216; p = .000< .05), price (Rho = 0.044; p = .385>0.05), place (Rho = 0.302; p = .000< .05) and promotion (Rho = 0.186; p = .000< .05). The findings of this study are relevant for companies in the sector, as they demonstrate a direct relationship between the variables analyzed and underline the importance of using green marketing strategies.
Keywords: Green Marketing; Environmental Awareness; Purchase Decision; Millennials.